1970
DOI: 10.1002/art.1780130304
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally induced corticosteroid arthropathy

Abstract: lntraarticular injections of triamcinolone acetonide resulted in deleterious changes in living rabbit articular knee cartilage. These changes were characterized by an increased frequency of chondrocyte nuclear degeneration and prominent cyst formation as compared with control animals. Degenerative changes were localized to the cartilage of the medial tibia1 plateau. This localization may be related to the different histologic pattern seen i n this cartilage surface as compared to other areas of the knee. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
5

Year Published

1972
1972
2002
2002

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 106 publications
(42 citation statements)
references
References 8 publications
1
36
0
5
Order By: Relevance
“…Such ulceration, when seen, consisted of loss of superficial layers of cartilage over a small area. Fissure formation was seen primarily on the medial tibial plateau and did not exceed that described previously in the normal rabbit knee (6).…”
Section: Histologic Examinationsupporting
confidence: 64%
See 1 more Smart Citation
“…Such ulceration, when seen, consisted of loss of superficial layers of cartilage over a small area. Fissure formation was seen primarily on the medial tibial plateau and did not exceed that described previously in the normal rabbit knee (6).…”
Section: Histologic Examinationsupporting
confidence: 64%
“…As in the partial meniscectomy series, changes were noted in femoral cartilage only. Fissure formation on both the femoral and tibial surface did not exceed that seen in normal rabbit knees (6). Diminished Safranin 0 stain was observed on the medial femoral condyle in 2 animals.…”
Section: Proliferation Of Chondrocytes In Clones (mentioning
confidence: 66%
“…The use of corticosteroids in OA remains controversial due to reports of a possible deleterious effect on cartilage (13)(14)(15). Further studies using an OA model that closely mimics the changes observed in the human disease are needed.…”
Section: Protective Effects O F Corticosteroids On Cartilage Lesions mentioning
confidence: 99%
“…Clinicians have also used intra-and periarticular corticosteroids for managing inflammation associated with both acute and chronic arthritic diseases [4143]. While these agents reduce expression of matrix metalloproteinases and are clearly helpful in relieving the symptoms of joint inflammation, experimental evidence suggests that corticosteroids damage articular cartilage independent of the disease process [27,35,39,45]. Pathological changes de-* Corresponding author.…”
Section: Introductionmentioning
confidence: 99%